2020
DOI: 10.2147/ott.s232953
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Promotion of miR-221-5p on the Sensitivity of Gastric Cancer Cells to Cisplatin and Its Effects on Cell Proliferation and Apoptosis by Regulating DDR1</p>

Abstract: Purpose: This research aimed to explore the role of miR-221-5p on the sensitivity of gastric cancer cells to cisplatin, and the proliferation and invasion of gastric cancer cells by regulating DDR1. Patients and Methods: Altogether 69 patients who treated with radical gastrectomy from January 2014 to January 2016 were collected. With the agree of the patients, 69 gastric carcinoma and 69 adjacent tissues were taken, respectively, during the operation, and gastric carcinoma and human gastric mucosa cells were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Luciferase reporter assay and RIP assay veri ed the prediction that RNF185-AS1 directly interacted with miR-221-5p. miR-221-5p has been reported to exerts tumor suppressive function in prostate cancer [17,18], gastric cancer [19] and colorectal cancer [20]. On the contrary, previous research have reported that miR-221-5p acted as an oncogene in several tumors, such as renal cell cancer [21], prostate cancer [22].…”
Section: Discussionmentioning
confidence: 98%
“…Luciferase reporter assay and RIP assay veri ed the prediction that RNF185-AS1 directly interacted with miR-221-5p. miR-221-5p has been reported to exerts tumor suppressive function in prostate cancer [17,18], gastric cancer [19] and colorectal cancer [20]. On the contrary, previous research have reported that miR-221-5p acted as an oncogene in several tumors, such as renal cell cancer [21], prostate cancer [22].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a negative correlation between miR-221-5p and DDR1 has been demonstrated. Overexpression of miR-221-5p in gastric cancer cells inhibits not only EMT, but also proliferation and invasion through modulation of DDR1 expression [ 103 ]. DDR1 induces EMT in hepatocellular carcinoma by regulating STAT3 in vitro and in vivo [ 35 ].…”
Section: Roles Of Ddrs In Cancer Progressionmentioning
confidence: 99%
“…In gastric cancer, miR-221-5p modulates DDR1 expression. When miR-221-5p is downregulated, DDR1 expression increases and promotes migration and invasion [ 103 ]. On the contrary, in pancreatic carcinoma, the interplay of DDR1 with E-cadherin and the Par3 signaling pathway was shown to prevent 3D invasion by enhancing cell–cell adhesion [ 114 ].…”
Section: Roles Of Ddrs In Cancer Progressionmentioning
confidence: 99%
“…It has been observed that there were significant miR-221-5p down regulations in GC tissues and cells. MiR-221-5p promoted apoptosis and cisplatin-sensitivity, while inhibited gastric tumor cell proliferation and migration through DDR1 targeting [ 50 ]. MET is also another RTK that is activated by hepatocyte growth factor (HGF) to regulate cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%